Single event effects instrumentation for system-on module testing - Mauricio Ernesto, RODRIGUEZ ALAS (2024)
Radiation testing and qualification of complex systems is a challenging and demanding process due to the interactions and dependencies between systems. This thesis presents the development of a low-cost, compact, robust, and highly synchronized testing instrument designed to standardize Single Events Effects testing for modern System-on-Chip devices. By increasing logging capabilities and timing synchronization, we can get better control over the systems under test. The instrumentation performance is demonstrated experimentally during a neutron irradiation campaign, showcasing its reliability and ability to improve complex system testing.